Indigenous Holophrasis as Ecological Poetics and Praxis in Contemporary Australian-Aboriginal and Southeast Asian Poems - Henrikus Joko Yulianto (Journal of Language and Literature, 2025)
Indigenous poetry correlates with oral form. It signifies shamanic mantra but embodies ecological wisdom since it mostly depicts human’s relationship with nature. This paper deals with contemporary English poems especially those of Australian-Aboriginal and Southeast Asian poems which make use of indigenous aspects in the form and content. The purpose of this research is to identify how the use of holophrasis is beneficial in highlighting the indigenous aspects in the poems. Among these poems include Evelyn Araluen and Lionel Fogarty, two contemporary Aboriginal poets who adopt Aboriginal phrases in their poems; Quintin Jose V. Pastrana, a young Philippine poet who was inspired by the Ambahan or the indigenous poetic form of the Hanunuo Mangyan people’s in Oriental Mindoro, the Philippines; and Mario F. Lawi, a young Indonesian poet from East Nusa Tenggara who illustrates the initiation rite of Nappu Pudi tribe in that island. This research used qualitative method by referring to holophrasis as the method and praxis in reading the native poems. By means of the holophrastic reading, I found that the use of indigenous elements in their poems serves as methods to aestheticize and indigenize the poems in order to assert native identity in the hegemony of English as the colonial language.